Awareness of Savings and Investment Options in Z Category Cities of India: A Study with Reference to Vellore City - Vedantam, Seetha Ram; G., Sriram (Indian Journal of Finance, 2015)
Domestic savings of a nation determine the strength of an economy. Over a decade, savings behaviour of individuals in small cities and towns has influenced the gross domestic savings of nations across the globe. This changing savings pattern has an influence on the investment patterns as well. Hence, to understand this, a study was conducted in a Z category city - Vellore , Tamil Nadu. The study aimed to understand the drift in savings and investment patterns, awareness about the modern means of savings and investment options, and how effective is the role of investment advisors in instrument selection. The data were collected through a structured questionnaire that was administered to the residents of Vellore city. The results were tested with statistical tools like analysis of variance (ANOVA) and chi-square. The results revealed that individuals of the city were quite aware of the difference between savings and investments, irrespective of their demographic aspects. However, proper guidance is needed, for which investment advisors need to take measures. In addition, similar studies need to be conducted at several places across India, and effective measures, such as implementation of Pradhan Mantri Jan Dhan Yojana and such others need to be promoted to improve the general public’s financial inclusion process in the Indian money market.